2013
DOI: 10.1136/bjophthalmol-2012-302066
|View full text |Cite
|
Sign up to set email alerts
|

Optic disc morphology in premature infants

Abstract: In our study, premature birth was associated with the presence of a double ring. A low birth weight and low gestational age influence the form of the optic disc.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
3
14
0
Order By: Relevance
“…Of the four published studies on infant ON parameters, 2, 11, 22, 23 none used OCT. Only Kandasamy et al 11 (n=35 term infants) assessed for relationships between ON measurements and parameters associated with preterm birth using Retcam, and found no association between low birth weight and disc area (Table 2). However, cup areas were not measured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the four published studies on infant ON parameters, 2, 11, 22, 23 none used OCT. Only Kandasamy et al 11 (n=35 term infants) assessed for relationships between ON measurements and parameters associated with preterm birth using Retcam, and found no association between low birth weight and disc area (Table 2). However, cup areas were not measured.…”
Section: Discussionmentioning
confidence: 99%
“…However, cup areas were not measured. 11 A study by Hackl et al 22 also attempted such measures but reported a high possibility of cup measurement error using Retcam photos.…”
Section: Discussionmentioning
confidence: 99%
“…However, a reduction in DA with increasing BW and GA and a reduction in RA with increasing BW were also found by Hellstr€ om and co-authors, when analysing fundus photographs ). In addition, a negative correlation between the optic disc size and GA and BW has been found in premature infants analysing wide-field images (RetCam; Hackl et al 2013). In contrast, Raffa et al (2016) described a positive correlation between DA and BW in their material of moderate-to-late-preterm children.…”
Section: Discussionmentioning
confidence: 99%
“…A low birth weight and low gestational age influence the form of the optic disc [3]. They found a significant negative correlation between the form of the optic disc and gestational age (P = 0.03); 75% of optic discs showed a double ring and 89% had visible disc cupping.…”
Section: Open Access Ojophmentioning
confidence: 97%
“…However, optic disc morphology and optic nerve development are two factors that potentially influence visual function in infants [3].…”
Section: Introductiomentioning
confidence: 99%